Utilization of Groundnut Shell Ash as Cement Replacement in Stabilized Earth Blocks - Vinusha, S.V.; Vithushan, P.A.; Sathiparan, N. (University of Ruhuna Sri Lanka, 2023)
This study analyzes the feasibility of using groundnut shell ash (GSA) obtained as the byproduct of agriculture in the manufacturing of stabilized earth blocks. Solid masonry blocks were casted with a mix proportion of 1:6 cement and sand. Cement blocks, at four different GSA as partial replacement levels of 0, 10%, 20%, 30%, and 40% were prepared as a fraction of cement weight. Experimental setups were conducted on the earth blocks including determining physical parameters such as densities and water absorption rates; mechanical characteristics including compressive strength and flexural strength; durability aspects such as sorption, and resistance against severe environmental conditions. Additionally, the cost, embodied energy, and CO2 emission for the production of earth blocks were estimated in order to assess the cost-benefit and sustainability of GSA incorporation in cement-sand blocks. Results from this test indicate that even though the mechanical properties of GSA cement blocks do not vastly improve the strength properties the durability characteristics of GSA cement blocks are slightly better and improve the sustainability of block production.
Keywords: Stabilized earth blocks; Cement; Groundnut shell ash; Strength; Durability; Sustainability